BE3 is the major branching enzyme isoform required for amylopectin synthesis in Chlamydomonas reinhardtii - Courseaux, Adeline; George, Océane; Deschamps, Philippe; Bompard, Coralie; Duchêne, Thierry; Dauvillée, David (Frontiers in Plant Science, 2023)
Starch-branching enzymes (BEs) are essential for starch synthesis in both plants and algae where they influence the architecture and physical properties of starch granules. Within Embryophytes, BEs are classified as type 1 and type 2 depending on their substrate preference. In this article, we report the characterization of the three BE isoforms encoded in the genome of the starch producing green algae Chlamydomonas reinhardtii: two type 2 BEs (BE2 and BE3) and a single type 1 BE (BE1). Using single mutant strains, we analyzed the consequences of the lack of each isoform on both transitory and storage starches. The transferred glucan substrate and the chain length specificities of each isoform were also determined. We show that only BE2 and BE3 isoforms are involved in starch synthesis and that, although both isoforms possess similar enzymatic properties, BE3 is critical for both transitory and storage starch metabolism. Finally, we propose putative explanations for the strong phenotype differences evidenced between the C. reinhardtii be2 and be3 mutants, including functional redundancy, enzymatic regulation or alterations in the composition of multimeric enzyme complexes